Analisis Pengaruh Strategi Pemasaran Terhadap Volume Penjualan pada UMKM Industri Bakery di Jawa Tengah - Miftahurrohman Miftahurrohman; Vivi Kumalasari Subroto (LPPM Politeknik Pratama, 2026)
The purpose of this study was to examine whether marketing strategy influences sales volume. The marketing strategy variables were product innovation, product quality, and promotion. The study used an associative quantitative approach, with 93 respondents from MSMEs in the bakery industry in Central Java serving as the sample. Data were collected through a questionnaire distributed to respondents using a Likert scale. Data analysis was performed using the Smart PLS application. The data analysis showed a significant relationship between product innovation and sales volume. However, the other variables, product quality and promotion, showed no relationship between product quality and sales volume, and no relationship between promotion and sales volume.